World cities and peripheral development: The interplay of gateways and subordinate places in Argentina and Ghana's upstream oil and gas sector - Sören Scholvin (Growth and Change, 2020)
Serving as “gateways”, some world cities tie their wider hinterlands to global networks. The article revisits gateway–hinterland relations against the backdrop of assessments that lead to opposed conclusions on the benefits and shortcomings of integration into the world economy. Referring to the oil and gas sector in Argentina and Ghana, it answers the question of how gateways interact with subordinate places and also uncovers obstacles to peripheral development. The author finds that Accra and Buenos Aires concentrate corporate control. Argentina's capital serves as a gateway for knowledge generation and logistics too. Opportunities for peripheral development in both countries are considerable, albeit largely limited to generic services. Besides a certain concentration of business activities in the gateway cities, more important challenges to peripheral development are typical for small and medium enterprises (insufficient finance and management capabilities, unawareness of business opportunities, and the like). They include rent seeking and subcontracting. The latter leaves local companies in a particularly weak position vis-à-vis lead firms. The author argues that while integration into the world economy allows for peripheral development, the corresponding outcomes may not meet everyone's expectations. Related expectations must, therefore, be more down-to-earth than overly optimistic statements frequently made by politicians.
Keywords: 300